Non-Invasive Breast Cancer Diagnosis through Electrochemical Biosensing at Different Molecular Levels - Campuzano, Susana (Sensors (Basel), 2017)
The rapid and accurate determination of specific circulating biomarkers at different molecular levels with non- or minimally invasive methods constitutes a major challenge to improve the breast cancer outcomes and life quality of patients. In this field, electrochemical biosensors have demonstrated to be promising alternatives against more complex conventional strategies to perform fast, accurate and on-site determination of circulating biomarkers at low concentrations in minimally treated body fluids. In this article, after discussing briefly the relevance and current challenges associated with the determination of breast cancer circulating biomarkers, an updated overview of the electrochemical affinity biosensing strategies emerged in the last 5 years for this purpose is provided highlighting the great potentiality of these methodologies. After critically discussing the most interesting features of the electrochemical strategies reported so far for the single or multiplexed determination of such biomarkers with demonstrated applicability in liquid biopsy analysis, existing challenges still to be addressed and future directions in this field will be pointed out.